2020
DOI: 10.1007/s00521-020-04853-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of correlation between the steels susceptibility to hydrogen embrittlement and hydrogen thermal desorption spectroscopy using artificial neural network

Abstract: Steels are the most used structural material in the world, and hydrogen content and localization within the microstructure play an important role in its properties, namely inducing some level of embrittlement. The characterization of the steels susceptibility to hydrogen embrittlement (HE) is a complex task requiring always a broad and multidisciplinary approach. The target of the present work is to introduce the artificial neural network (ANN) computing system to predict the hydrogen-induced mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…MAE of the HSP prediction using the developed ANN model at the test dataset was calculated to be about 1.4%. The advantage of the proposed measurement data processing is obvious considering our previous study, where MAE was calculated to be about 2.8% and 4.5% for feed-forward and convolutional neural network architectures, respectively [15]. The detailed study of the prediction error calculated at the test dataset for individual steels showed some increase of MAE calculated for steels included in the validation compared to those used in the model learning process (see Figure 7).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…MAE of the HSP prediction using the developed ANN model at the test dataset was calculated to be about 1.4%. The advantage of the proposed measurement data processing is obvious considering our previous study, where MAE was calculated to be about 2.8% and 4.5% for feed-forward and convolutional neural network architectures, respectively [15]. The detailed study of the prediction error calculated at the test dataset for individual steels showed some increase of MAE calculated for steels included in the validation compared to those used in the model learning process (see Figure 7).…”
Section: Resultsmentioning
confidence: 73%
“…where x i is the descriptor parameter of the artificial spectroscopy data. F(x i ) is a linear function defined by the fitting of the relationship between x i = [1,3] and x i = [4,15] . It is worth noting that the Pearson correlation coefficients between only the same type of descriptor parameters defining the peak height, temperature position, and width were considered.…”
Section: Measurement Data Processingmentioning
confidence: 99%
See 3 more Smart Citations